Influence of cutting clearance and punch geometry on the stress state in small punch test - Otroshi, Mortaza; Meschut, Gerson (Engineering Failure Analysis)
The presented paper aims to characterize the damage and fracture behavior of HX340LAD Micro-Alloyed steels using small punch test. Variations with respect to punch geometries and cutting clearance are made to describe the damage behavior of the material under different loading conditions. Experimental investigations are conducted to identify the crack initiation in the specimens. Furthermore, the numerical FEM simulations are performed to identify the stress state at crack initiation. It is shown that different stress states from shear to biaxial tension can be achieved by changing the geometries of punch and varying the cutting clearance. Moreover, it is presented how changing the configurations can influence the stress state variables: Triaxiality and lode angle parameter.
Keywords: Ductile damage; stress state; small punch test; triaxiality; lode angle parameter

Systematisierung einer rechnergestützten Auswertemethode zur Versagensanalyse geklebter Verbindungen - Chudalla, Nick; Teutenberg, Dominik; Meschut, Gerson; Schneider, Miriam; Smart, Dominik (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Efficient Frequency Conversion with Geometric Phase Control in Optical Metasurfaces - Reineke Matsudo, Bernhard; Sain, Basudeb; Carletti, Luca; Zhang, Xue; Gao, Wenlong; Angelis, Costantino; Huang, Lingling; Zentgraf, Thomas (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Development of a rivet geometry for solid self-piercing riveting of thermally loaded CFRP-metal joints in automotive construction - Vorderbrüggen, Julian; Köhler, Daniel; Grüber, Bernd; Troschitz, Juliane; Gude, Maik; Meschut, Gerson (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Consideration of the manufacturing history of sheet metal components for the adaptation of a clinching process - Heyser, Per; Wiesenmayer, S; Frey, P; Nehls, T; Scharr, C; Flügge, W; Merklein, M; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
The process chain for the manufacturing of sheet metal components in mass production includes various cutting and forming operations, which influence the resulting properties of the parts and therefore subsequent manufacturing steps, such as clamping and joining. It is shown that clamping of the components leads to superimposed residual stresses and geometry changes. Therefore, the part properties differ from the initial state of the semifinished products, which has to be considered in the design of clinched joints. This paper presents an approach for coupled determination of the properties of semifinished and finished parts during deep drawing and clamping as well as their effects on the joint quality during clinching. One method for the effective and efficient determination of the properties of semifinished products and components during production is using process data from the preceding manufacturing processes, which is concretely presented in this work. In addition to the interconnection of the entire production chain, it is necessary to define relevant process data for each individual manufacturing step and to correlate the data with the material properties reliably. Therefore, the cross-process interactions of different steps of the process chain for the manufacturing of sheet metal components and the effect of process variations on subsequent manufacturing steps are investigated. Consequently, the boundary conditions for a mechanical joining process based on data from preceding process steps can be predicted.
Keywords: Mechanical Engineering; General Materials Science

Self-Adaptive Digital Assistance Systems for Work 4.0 - Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Digital Transformation: Core Technologies and Emerging Topics from a Computer Science Perspective)

Spin-Orbit Interaction of Light Enabled by Negative Coupling in High-Quality-Factor Optical Metasurfaces - Gao, Wenlong; Sain, Basudeb; Zentgraf, Thomas (Physical Review Applied)
Keywords: General Physics and Astronomy

Output feedback control with prescribed performance via funnel pre-compensator - Lanza, Lukas Johannes (Mathematics of Control, Signals, and Systems)
We study output reference tracking of systems with high relative degree via output feedback only; this is, tracking where the output derivatives are unknown. To this end, we prove that the conjunction of the funnel pre-compensator with a minimum phase system of arbitrary relative degree yields a system of the same relative degree which is minimum phase as well. The error between the original system's output and the pre-compensator's output evolves within a prescribed performance funnel; and moreover, the derivatives of the funnel pre-compensator's output are known explicitly. Therefore, output reference tracking with prescribed transient behavior of the tracking error is possible without knowledge of the derivatives of the original system's output; via funnel control schemes for instance.

Integrating Safety Guarantees into the Learning Classifier System XCS - Hansmeier, Tim; Platzner, Marco (Applications of Evolutionary Computation, EvoApplications 2022, Proceedings)

Bauteilschonendes Entfügen struktureller Klebverbindungen durch Kälte - Chudalla, Nick; Meschut, Gerson; Bartley, Aurélie; Wibbeke, Tim Michael (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Coordinating Amoebots via Reconfigurable Circuits - Feldmann, Michael; Padalkin, Andreas; Scheideler, Christian; Dolev, Shlomi (J. Comput. Biol.)

Environment‐Dependent Stability and Mechanical Properties of DNA Origami Six‐Helix Bundles with Different Crossover Spacings - Xin, Yang; Piskunen, Petteri; Suma, Antonio; Li, Changyong; Ijäs, Heini; Ojasalo, Sofia; Seitz, Iris; Kostiainen, Mauri A.; Grundmeier, Guido; Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Experimentelle Untersuchung und Modellvalidierung zur Gravidestillation - Wende, Marc; Fischer, Florian; Kenig, Eugeny (Jahrestreffen der ProcessNet Fachgruppen Fluidverfahrenstechnik und Hochdruckverfahrenstechnik)

Influence of process parameters on the formation of inhalable fiber dust during shredding for mechanical recycling of fiber‐reinforced organo sheets - Hopp, Matthias; Tölle, Lisa (Journal of Applied Polymer Science)

Fiber Dust Formation during the Recycling of FRP - Hopp, Matthias; Tölle, Lisa; Bünger, J.; Westphal, G.; Rosenkranz, N.; Monsé, C. (Kunststoffe international)

Faserstäube beim FVK-Recycling - Hopp, Matthias; Tölle, Lisa; Bünger, J.; Westphal, G.; Rosenkranz, N.; Monsé, C. (Kunststoffe)

Computation on Encrypted Data Using Dataflow Authentication - Fischer, Andreas; Fuhry, Benny; Kußmaul, Jörn; Janneck, Jonas; Kerschbaum, Florian; Bodden, Eric (ACM Transactions on Privacy and Security)
Encrypting data before sending it to the cloud ensures data confidentiality but requires the cloud to compute on encrypted data. Trusted execution environments, such as Intel SGX enclaves, promise to provide a secure environment in which data can be decrypted and then processed. However, vulnerabilities in the executed program give attackers ample opportunities to execute arbitrary code inside the enclave. This code can modify the dataflow of the program and leak secrets via SGX side channels. Fully homomorphic encryption would be an alternative to compute on encrypted data without data leaks. However, due to its high computational complexity, its applicability to general-purpose computing remains limited. Researchers have made several proposals for transforming programs to perform encrypted computations on less powerful encryption schemes. Yet current approaches do not support programs making control-flow decisions based on encrypted data. We introduce the concept of dataflow authentication (DFAuth) to enable such programs. DFAuth prevents an adversary from arbitrarily deviating from the dataflow of a program. Our technique hence offers protections against the side-channel attacks described previously. We implemented two flavors of DFAuth, a Java bytecode-to-bytecode compiler, and an SGX enclave running a small and program-independent trusted code base. We applied DFAuth to a neural network performing machine learning on sensitive medical data and a smart charging scheduler for electric vehicles. Our transformation yields a neural network with encrypted weights, which can be evaluated on encrypted inputs in \( 12.55 \,ms \) . Our protected scheduler is capable of updating the encrypted charging plan in approximately 1.06 seconds.
Keywords: Safety; Risk; Reliability and Quality; General Computer Science

Conditional Beta-Convergence by Gravity - Stöckmann, Nico (Theoretical Economics Letters)

Verteiltes Berechnen kompakter Routingtabellen in Unit Disk Graphen - Hillebrandt, Henning

Realization of Exciton‐Mediated Optical Spin‐Orbit Interaction in Organic Microcrystalline Resonators - Ren, Jiahuan; Liao, Qing; Ma, Xuekai; Schumacher, Stefan; Yao, Jiannian; Fu, Hongbing (Laser & Photonics Reviews)